Analisis Kepuasan Nasabah terhadap Layanan Pembukaan Rekening Melalui Mobile Banking Bank Syariah Indonesi - Sherli Monika; Saparuddin (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2024)
Abstract This study aims to analyze customer satisfaction with account opening through mobile banking at Bank Syariah Indonesia. The method used is a survey with a questionnaire distributed to customers who have used the service. Data collected using statistical methods to convey various aspects of satisfaction, including ease of use, speed of process, and quality of customer service shows that most customers are satisfied with the account opening service through mobile banking, with positive assessments on ease of access and time efficiency of clarity of information and technical support. The conclusion of this study provides improved features and communication for more.